RECICLAR RECORDAÇÕES COM AS CIÊNCIAS - PERCURSOS DE APRENDIZAGEM EM CONTEXTO DE JARDIM-DE-INFÂNCIA - Ferreira, Maria Eduarda Roque; Cepa, Carla; Tracana, Rosa; Reis, Carlos Francisco (Revista Contexto & Educação, 2017)